Cytoreductive Surgery Plus Platinum‐Based Hyperthermic Intraperitoneal Chemotherapy in Epithelial Ovarian Cancer: A Promising Integrated Approach to Improve Locoregional Control. (23rd March 2016) - Petrillo, Marco; Anchora, Luigi Pedone; Scambia, Giovanni; Fagotti, Anna
Abstract : Epithelial ovarian cancer (EOC) remains the most lethal among gynecological malignancies. Evidence strongly suggests that administration of platinum‐based hyperthermic intraperitoneal chemotherapy after cytoreductive surgery may represent an effective strategy to adequately treat both visible and microscopic disease, thus improving locoregional control.